2021
DOI: 10.3390/membranes11090660
|View full text |Cite
|
Sign up to set email alerts
|

Microcrystalline Cellulose-Blended Polyethersulfone Membranes for Enhanced Water Permeability and Humic Acid Removal

Abstract: A novel polyethersulfone (PES)/microcrystalline cellulose (MCC) composite membrane for humic acid (HA) removal in water was fabricated using the phase inversion method by blending hydrophilic MCC with intrinsically hydrophobic PES in a lithium chloride/N,N-dimethylacetamide (LiCl/DMAc) co-solvent system. A rheological study indicated that the MCC-containing casting solutions exhibited a significant increase in viscosity, which directly influenced the composite membrane’s pore structure. Compared to the pristin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…Contrary, the porosity of 4 wt% MCC/TEOS-based PVDF membrane was dramatically decreased to 71.8%. Due to the agglomeration of higher concentration of MCC/TEOS might be generated the specific bounds between MCC/TEOS and PVDF, resulting to limitation of membrane performance [35].…”
Section: Mcc/teos-based Pvdf Separator Membranes Characterizationsmentioning
confidence: 99%
“…Contrary, the porosity of 4 wt% MCC/TEOS-based PVDF membrane was dramatically decreased to 71.8%. Due to the agglomeration of higher concentration of MCC/TEOS might be generated the specific bounds between MCC/TEOS and PVDF, resulting to limitation of membrane performance [35].…”
Section: Mcc/teos-based Pvdf Separator Membranes Characterizationsmentioning
confidence: 99%
“…For cellulosic materials, the two main mechanisms involved in the removal of heavy metal ions are ion exchange and chemical complexation mechanisms [ 339 ]. Cellulose materials possess excellent hydrophilicity due to the presence of -OH groups on their surface, making them perfect additives for TFNC membranes [ 340 ]. Hoang et al deposited cellulose nanocrystals (CNC) as an interlayer on PES substrate and a barrier layer was fabricated using the IP method.…”
Section: Incorporation Of Nps In Tfncs/mmmsmentioning
confidence: 99%
“…Nazri et al incorporated microcrystalline cellulose (MCC) into hydrophobic PES matrix using the NIPS method and found that 3 wt.% MCC resulted in improved water permeability (51.50 ) compared to the pristine membrane and a 96.14% humic acid rejection. Although the inclusion of MCC results in a better PI rate, leading to elongated and bigger pore sizes benefiting the flux response, it is important to note that 3 wt.% loading also reduced the tensile strength (6.57 → 5.71 MPa) compared to the pristine membrane due to an aggregation issue in the casting solution [ 340 ]. Other studies have shown better flux responses, 485 [ 344 ] and 692 [ 345 ], when using CNC and lignin cellulose nanofibrils in the PES membrane in the presence of PVP additive, which adds to the pore-forming property and reduce the aggregation of NPs.…”
Section: Incorporation Of Nps In Tfncs/mmmsmentioning
confidence: 99%
“…A polyethersulfone (PES)/microcrystalline cellulose (MCC) composite membrane for humic acid (HA) removal in water was made by Nazri et al [107] using the phase inversion method. A rheological study showed that MCC-containing casting solutions increased viscosity, affecting the composite membrane's pore structure.…”
Section: Technique Principlementioning
confidence: 99%